The Importance of The Dental Hygienist in Implantology: A Narrative Review - Lucia Caporaso; Alessandra Bissoli; Francesca Iarussi; Riccardo Pulcini; Marco Dolci; Silvia D'Agostino (Pandawa Institute, 2022)
Dental implants have become a standard treatment in the replacement of missing teeth. If maintaining good oral health in a mouth without prosthetic elements requires proper self oral hygiene and professional maintenance, preserving implant health requires even more accuracy and consistency. Dental hygienists are fundamental in the management of the bacterial biofilm, in the context of prevention, education and professional treatment of the patient. This review explores the importance and the role of the dental hygienist in oral implantology.